The thinking hand : existential and embodied wisdom in arthitecture - Pallasmaa, Juhani, 1936- (Chichester, U.K. : Wiley, 2009)
Surveys the multiple essences of the hand, its biological evolution and its role in the shaping of culture, highlighting how the hand-tool union and eye-hand-mind fusion are essential for dexterity and how ultimately the body and the senses play a crucial role in memory and creative work.
boek